here's the equation: \({-z + 4z} = {4}\) , and please show step by step on how to do it

Guest Feb 19, 2018

edited by
Guest
Feb 19, 2018

edited by Guest Feb 19, 2018

edited by Guest Feb 19, 2018

#2**+1 **

Since you are looking for a vertex form, I assume you are starting with a QUADRATIC:

-z^2 + 4z =4

-z^2 +4z-4 = 0 we want a(z-h)^2 +k =0 form

-1 (z^2 -4z +4) = 0 'complete the square'

-1 {(z-2)^2 +4 -4} = 0

-1 (z-2)^2 +0 = 0 is the vertex form where vertex is 2, 0

ElectricPavlov
Feb 19, 2018